Improving the Students’ Listening Ability through Broadcast Voice of America (VOA) Learning English to the Second Grade Students of SMAN 1 Peusangan Siblah Krueng - Yunita, Irma Yunita; Chalil As’ari (Journal of English Education and Social Science, 2022)
This study describes classroom action research conducted in the second grade of SMAN 1 Peusangan Siblah Krueng to improve students' listening Ability through the application of Broadcast Voice of America (VOA) Learning English as a media. The research method used in this class is a collaborative classroom action research method by collaborating with the English teacher at SMAN 1 Peusangan Siblah Krueng. This classroom action research was carried out in two cycles. Each cycle consists of 4 stages, namely the planning stage, the implementation stage, the observation stage and finally the reflection stage. To obtain data in this study, qualitative and quantitative data were used as seen from various activities carried out in improving listening ability through the application of Broadcast Voice of America (VOA) Learning English. The purpose of this research is to know Broadcast Voice of America (VOA) Learning English improve the students listening ability, to know the students’ response toward in listening ability after using Broadcast Voice of America (VOA) Learning English, and to find out the teacher performance in teaching and learning process by the implementation of Broadcast Voice of America (VOA) Learning English.